2010
DOI: 10.1021/ie100568z
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of Coal-Based Hydrogen and Electricity Cogeneration Processes with CO2 Capture

Abstract: The techno-economic performances of various coal-based hydrogen and electricity cogeneration processes are examined under a carbon-constrained scenario. The baseline coal gasification process and the novel membrane and syngas chemical-looping processes are evaluated. Aspen Plus simulation is first performed to analyze the process efficiencies on the basis of a common set of assumptions. This is followed by economic analysis using the cost analysis principles suggested by the U.S. Department of Energy [Cost and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…It shows steady, continuous, high‐purity CO 2 and H 2 generation from the reducer and oxidizer gas outlets, respectively. Analysis of the OSU SCL process has shown that it can reduce the cost of electricity production with CO 2 capture by 11% and the cost of H 2 production by 7–9% over the corresponding baseline cases …”
Section: Osu Chemical‐looping Technologiesmentioning
confidence: 99%
“…It shows steady, continuous, high‐purity CO 2 and H 2 generation from the reducer and oxidizer gas outlets, respectively. Analysis of the OSU SCL process has shown that it can reduce the cost of electricity production with CO 2 capture by 11% and the cost of H 2 production by 7–9% over the corresponding baseline cases …”
Section: Osu Chemical‐looping Technologiesmentioning
confidence: 99%
“…The following section analyzes the performance of the iron based syngas chemical looping process. 109 Several other potential Type I looping process configurations for hydrogen production are also discussed.…”
Section: Chemical Looping Processesmentioning
confidence: 99%
“…As the most abundantly reserved fossil fuel, coal remains an important energy and carbonaceous material source today and will be for the foreseeable future. Compared to other fossil fuels such as crude oil and natural gas, coal is more carbon intensive, [ 1 ] and therefore determining how to utilize the vast reserves more efficiently and less carbon emission has been a challenge. Gasification technology has been developed worldwide for more efficient and clean use of coal as a feedstock and energy resource.…”
Section: Introductionmentioning
confidence: 99%